THE EFFECT OF THE PROBLEM BASED LEARNING MODEL ASSISTED BY AUDIO VISUAL MEDIA ON THE ACTIVITY AND LEARNING OUTCOMES OF CLASS V STUDENTS IN THE SOCIAL STUDIES CONTENT ECONOMICACTIVITY MATERIAL AT UPT SPF SD NEGERI MANGKURA I MAKASSAR - Niar Niar; Yunus Yunus; Muh. Yahya (INJOSEDU: International Journal of Social and Education, 2025)
This research aims to know the description of student activity and learning outcomes before and after using the Problem Based Learning learning model assisted by audio- visual media on social studies content economic activity material.This research is a quantitative research type of Quasi Experimental Design with Nonequivalent Control Group Design type. results Student learning activity in the experimental class increased from a pretest score of 62.5 to 86.25 in the posttest. Meanwhile, in the control class, the pretest score for student learning activity was 66.67 to 70.83 in the posttest. The social studies learning outcomes of students in the experimental class increased significantly from the pretest score of 48.5 to 89.75 in the posttest. Meanwhile, in the control class, the pretest learning outcomes score was 55.75 to 66.50 in the posttest. There is an influence of the application of the problem-based learning model assisted by audio-visual media on the activeness of learning social studies class V economic activity material with social studies content ,There is an influence of the application of the problem based learning model assisted by audio visual media on the learning outcomes of class V social studies material on economic activities with social studies.